Students’ Attitude Towards Learning ‘Bahasa Inggris’ Course - Yasminar Amaerita Telaumbanua (TEHUDE: Jurnal Ilmiah Pendidikan Bahasa Inggris, 2023)
Students‟ attitude nowadays is very important to be searched since it is very crucial in academic field. Almost all teachers in education complained of the students‟ attitude towards teaching-learning process in classrooms. Objective of the study was to describe students‟ attitude towards teaching learning process particularly when learning Bahasa Inggris course. Research method was qualitative research. Participants in the research was second semester students of Civics Education of Universitas Nias with total number of students were 47 persons. The research was conducted during one semester wherein teacher-researcher as the teacher for teaching Bahasa Inggris course in the class. The second semester students were observed by the teacher-researcher and having talks directly in the classroom with the teacher-researcher to talk their attitude towards the teaching-learning process. Then questionnaire was distributed to them. Since the beginning of class, it was found, there was no any positive change towards their attitude to learn Bahasa Inggris course. The findings were contrast obtained from the two research instruments. Of the contrast findings, it was stated that the second semester students had problem with the two of four characteristics of attitude, two concepts of attitude and cognitive dissonance beside self-interest and lack of self-awareness. As a conclusion, mostly the second semester students of Civics Education have negative attitude towards the teaching-learning process particularly in Bahasa Inggris course because of cognitive dissonance beside self-interest and lack of self-awareness.